FREQUENCY OF HELICOBACTER PYLORI IN DISTAL OESOPHAGEAL MUCOSA OF PATIENTS WITH DYSPEPSIA - Bashir, Tahir; Nadeem, Muhammad Arif; Nisar, Sajid; Randhawa, Fawad Ahmad; Pervaiz, Abida (Journal of Ayub Medical College Abbottabad, 2014)
Background: Helicobacter pylori (H. pylori) is one of the common causes of dyspepsia. The present study was conducted to find the frequency of H. pylori in the distal oesophageal mucosa of patients with dyspepsia. Methods: This descriptive cross sectional study was conducted in Services Hospital Lahore. History and physical examination was recorded and after informed consent oesophagoduodenoscopy of all the patients with the symptoms of dyspepsia was done. Findings were noted and gastric antral and distal oesophageal biopsies taken simultaneously. Both specimen were preserved in 10% formalin and sent for histopathological examination for the presence of H. pylori. Results: Out of the 116 patients, 16 patients were between ages 16-30, 82 patients were between ages 31-45 years and 18 were over 45 years of age. Thus percentage of subjects between 31-45 years was maximum i.e., 70.68%. Seventy-six (65.5%) of the patientswere male and 40 (34.5%) were females.The H pylori was found in 40 (34.5%) patients in gastric antral biopsy and it was isolated in only 14 (12.1%) patients in distal esophageal biopsies.Conclusion: H. pylori positivity was low in the distal oesophageal mucosa of patients with dyspepsia despite its presence in gastric mucosa. A close relationship could not be established between H. pylori in the distal oesophagus and gastric antral mucosa in dyspeptic patients. Based on these findings, it seems that there is no significant evidence for an important pathogenic role for H. pylori infection in the development of pathologic dyspepsia and chronic gastroesophageal reflux disease. Keywords: Helicobacter pylori, dyspepsia, reflux, gastroesophageal